ESGO/ESTRO/ESP guidelines for the management of patients with endometrial carcinoma. Issue 1 (January 2021) - Concin, Nicole; Matias‐Guiu, Xavier; Vergote, Ignace; Cibula, David; Mirza, Mansoor Raza; Marnitz, Simone; Ledermann, Jonathan; Bosse, Tjalling; Chargari, Cyrus; Fagotti, Anna; Fotopoulou, Christina; Martin, Antonio Gonzalez; et al.
Abstract : N/A: A European consensus conference on endometrial carcinoma was held in 2014 to produce multi‐disciplinary evidence‐based guidelines on selected questions. Given the large body of literature on the management of endometrial carcinoma published since 2014, the European Society of Gynaecological Oncology (ESGO), the European SocieTy for Radiotherapy and Oncology (ESTRO), and the European Society of Pathology (ESP) jointly decided to update these evidence‐based guidelines and to cover new topics in order to improve the quality of care for women with endometrial carcinoma across Europe and worldwide.